The anticipation of Malaysian urban cities to be Inclusive and accessible by 2030 - Abd Samad, Nur Amirah; Abdul Rahim, Asiah (IIUM Press, International Islamic University Malaysia, 2019)
Malaysia, in the Malaysia Urban Forum (MUF) 2019 aims to realize the vision of the World Urban Forum (WUF) 2018 theme of ‘Cities 2030, Cities for All: Implementing the New Urban Agenda’ that is in line with Sustainable Development Goals (SDG). The introduction of the Malaysian Standard started in 1990 but not acknowledged until the establishment of the Persons with Disabilities Act in 2008 and gazetted in the Uniform Building By-Laws (UBBL) amendments despite the slow pace of accessibility awareness in urban development and implementation. The methodology compares the establishment of notable Inclusive and Accessible Cities with their planning strategies of implementing Universal Design. Findings and results will determine inclusive city’s strategies from each case study documented and device a framework of projection for cities’ inclusivity. Conclusively, this study would determine the anticipation of Malaysian urban cities to be Inclusive and Accessible in 2030 by strategising action plans and a framework for ten (10) year planning.